Craniospinal Irradiation with Spinal IMRT to Improve Target Homogeneity - Panandiker, Atmaram Pai (2007)
PURPOSE: To report a new technique for the spinal component of craniospinal irradiation (CSI) in the supine position, to describe a verification procedure for this method, and to compare this technique to conventional plans. METHODS AND MATERIALS: Twelve patients were treated between 1998 and 2006 with CSI using a novel technique. Sixteen children were treated with a conventional field arrangement. All patients were followed for outcomes and toxicity. CSI was delivered using a posterior-to-anterior (PA) intensity-modulated radiation therapy (IMRT) spinal field matched to conventional, opposed lateral cranial fields. Treatment plans were generated for each patient using the IMRT technique and a standard PA field technique. The resulting dosimetry was compared to determine target homogeneity, maximum dose to normal tissues, and total monitor units delivered. RESULTS: Evaluation of the spinal IMRT technique compared to a standard PA technique reveals a 7% reduction in the target volume receiving ≥110% of the prescribed dose and an 8 % increase in the target volume receiving ≥ 95% of the prescribed dose. While target homogeneity was improved, the maximum dose delivered in the paraspinal muscles was increased by approximately 8.5 % with spinal IMRT compared to the PA technique. Follow-up evaluations revealed no unexpected toxicity associated with the IMRT technique. CONCLUSIONS: A new technique of spine IMRT is presented in combination with a quality assurance method. This method improves target dose uniformity compared to the conventional CSI technique. Longer follow-up will be required to determine any benefit with regard to toxicity and disease control.